Family biking : - Hurst, Robert (FalconGuides, 2016)
Family Biking is a guide for parents and parents-to-be on how to introduce their children to the joys and responsibilities of bicycle riding. The guide includes safe methods of transporting children via trailer bike or tandems, taking young children on bicycle tours, fitting a child to a bicycle, teaching all aspects of bicycle safety, as well as how to deal with dangerous or potentially dangerous situations. It also includes how to teach children to care for their own bicycle, how to dress, how to carry things on their bicycle, and how to perform basic maintenance and repairs.